Culture of development and developmental capacity of states: The korean case - (:unkn) unknown (IGI Global, 2015)
The main premise of this chapter is that state actions are crucial for economic development and those actions are partly shaped by the culture. Because some cultures are more conducive to development, it is engaged with the question: "Would it be possible to direct cultural change to serve economic development" Since culture is a subject-object relationship, it might be possible to direct cultural change and consequently build up a developmental state. This chapter particularly focuses on the defining characteristics of a developmental state. In addition to the three characteristics recognized in the literature (relative autonomy, capacity, and embeddedness), four others are identified which are essential for a state to become developmental and remain so. These are: legitimacy of the state, integration of the society, socio-political stability, and motivation for economic development. The Korean developmental state is taken as a case study and investigated under this new light. © 2015 by IGI Global. All rights reserved.